2012
DOI: 10.1159/000341247
|View full text |Cite
|
Sign up to set email alerts
|

From Mitochondrial Disturbances to Energy Requirements

Abstract: An organism requires nutrients to produce ATP, but the substrate oxidative process increases oxidative stress. This fine-tuning is centralized in the mitochondria, which is able to react to any excess or deprivation in nutrients. In normal subjects, these regulations can induce inflammatory effect and obesity in energy excess and a decrease in oxidative stress in a hypocaloric diet. In the critically ill patient, the mitochondrial capacity to cope with severe illness not only includes oxygen supply and nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Whereas high WC is complementary to BMI [20] in the application of these new measures, the case of our background, which confirms that the first step to determine excess weight is to calculate ideal body weight [21] correlates to BFP or BMI levels. Account by Wener W.K.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Whereas high WC is complementary to BMI [20] in the application of these new measures, the case of our background, which confirms that the first step to determine excess weight is to calculate ideal body weight [21] correlates to BFP or BMI levels. Account by Wener W.K.…”
supporting
confidence: 67%
“…Sight the concept, which describes the ideal body weight at a minimum essential fat [45]. We admit the indication; which agrees; to determine excess weight gain total or partial (fat or fatness); the first step is to calculate ideal body weight [21]. Largely replaced by the use of the body mass index, calculation of percent IBW as another approach used for classification of people as overweight, obese, or underweight according to Sareen S. Gropper, et al [46].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the depth of sedation progressively decreases resting energy expenditure in postoperative patients 40 . The high degree of unintended overfeeding in critically ill children in our study is worrying and may influence clinical outcomes 41 , 42 . At the same time, a number of barriers to nutrition support were identified as causes of the discrepancy between prescribed and delivered nutrition.…”
Section: Discussionmentioning
confidence: 65%
“…Besides it should not be forgotten that many diseases accompany the obesity as well. A number of studies have demonstrated that many proteins and lipids that cause oxidative stress increase in endothelial cells of the patients with chronic diseases [4][5][6][7][8].…”
Section: Open Accessmentioning
confidence: 99%
“…Being able to react to any deficit or excess in energy and regulating ATP production, mitochondria play an important role in this equilibrium. Mitochondrial oxidative phosphorylation is responsible for 90% of total oxygen consumption and ATP generation [4].…”
Section: Introductionmentioning
confidence: 99%